New species in the Neotropical genus Docalidia with a key to known species, notes on distribution, taxonomy and a synoptic catalogue of the genus (Hemiptera: Cicadellidae: Coelidiinae: Teruliini) - Nielson, M. W. (Zootaxa, 2011)
Thirty-five new species of Docalidia in the tribe Teruliini are elucidated with descriptions, illustrations and photographs of the dorsal habitus. These include the following: Docalidia accurationis, sp. nov., D. acuminata, sp. nov., and D. rondoniensis, sp. nov. from Brazil; D. acutula, sp. nov., D. barbata, sp. nov., D. biarcua, sp. nov., D. caudata, sp. nov., D. cirra, sp. nov., D. cornicula, sp. nov., D. cornipes, sp. nov., D. curvatura, sp. nov., D. dennisi, sp. nov., D. deitzi, sp. nov., D. dietrichi, sp. nov., D. dmitrievi, sp. nov., D. fastigata, sp. nov., D. gigantea, sp. nov., D. goncalvesae, sp. nov., D. jonesi, sp. nov., D. mejdalanii, sp. nov., D. parvitatis, sp. nov., D. takiyae, sp. nov., D. timothyi, sp. nov., D. turgida, sp. nov., D. ventroelongata, sp. nov. and D. zhangi, sp. nov. from Colombia; D. bolivari, sp. nov., D. exilitis, sp. nov., D. torquerta, sp. nov. and D. ventrospinata, sp. nov. from Bolivia; D. longiuscula, sp. nov., D. mckameyi, sp. nov., D. tantula, sp. nov. and D. zahniseri, sp. nov. from Ecuador and D. longula, sp. nov. from Peru. Docalidia aculeata Nielson is fixed as the correct spelling for this species name, erroneously spelled as Docalida acus in the abstract and figure legend of the original publication. Docalidia acus is declared a nomen nudum. An updated, synoptic catalogue of all names applicable to Docalidia is given in alphabetical order with new annotations with distribution. A revised key to 174 of 178 known species is also provided.